Análogos experimentais de reforçamento negativo em metacontingências - Saconatto, André Thiago (2012)
The goal of this study was to create a experimental analogue of negative reinforcement in metacontingencies. To achieve this goal, were carried out two experiments which used academic students as participants which were distributed in generations of three subjects each and the most ancient one in the experimental session was exchanged by a naive one throughout the experiment and each exchange was caracterized as a generation change. Each participant had to perform a task, which was to insert numbers from zero to nine in the empty boxes on the program s screen. In the first experiment the points were obtained through positive reinforcement, the criterion to obtain points were that the sum of the numbers inserted by the participants with the numbers presented by the program resulted in a uneven number in each of the columns. The bonus operated in a negative reinforcement analogue, the criterion which avoided the bonus loss were that the sum of the numbers inserted by the participant, in the last two generations, a extinction phase was conducted. In the second experiment, the poins operated on negative reinforcement, the criterion which avoid the point loss were the same criterion which produced points in the first experiment. The bonus operated in a positive reinforcement analogue, the criterion which produced bonus was the same which avoided the bonus loss in the first experiment. The selection by/of metacontingencies occurred in the seventh generation on the first experiment and on the first generation on the second experiment. In both experiments in the extinction phases the interlocking contingencies which was selected did not occurred